SEISMIC HAZARD ASSESSMENT IN THE NORTH AEGEAN TROUGH BASED ON A NEW SEISMOGENIC ZONATION - Stylianou, E; Maravas, G; Kouskouna, V; Papoulia, J (Bulletin of the Geological Society of Greece, 2016)
The quantification of uncertainties and choise of the seismogenic zonation are crucial points in the probabilistic assessment of seismic hazard. This study followed the structure of a "logic tree" of 16 branches, in order to quantify uncertainties. It consists of two seismogenic zonations - one specifically developed for the North Aegean Trough based on recent swath mapping, geophysical and seismotectonic data, and the regional zonation used in the seismic hazard map of Greece. Two different approaches for the seismicity model definition and four attenuation relationships valid for Greece were used. The assessment of seismic hazard was obtained using the CRISIS software. All seismic hazard maps refer to the horizontal peak ground acceleration (PGA) with 475 years return period. Using the new developed zonation, maximum PGA values of 300 Gal are associated with the North Sporades area and the deepest part of the North Sporades basin. Results obtained by the regional seismogenic zonation of Greece shift maximum PGA values northeast of Athos peninsula. We conclude that the new zonation produces results that better address the seismotectonic regime of the North Aegean area.